2018
DOI: 10.22434/ifamr2017.0039
|View full text |Cite
|
Sign up to set email alerts
|

Customer experience with farmers’ markets: what hashtags can reveal

Abstract: Social media networks are increasing in popularity and have been integrated into many aspects of daily life. Analysis of the ways in which individuals use social media is important for understanding social, cultural, and environmental issues. This study examines experiences of farmers’ market customers through their self-expression on social networks. Contributions to the Instagram social network based on the #farmersmarket hashtag were gathered on a single day, yielding 19,398 contributions created by 13,862 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 75 publications
2
32
0
1
Order By: Relevance
“…They may be active on standard social networks such as Twitter and Instagram or on discussion forums [38], or they may insert their comments into articles in on-line news sites [39]. Such activities in social media take the form of expressing one's opinions, describing experiences, informing others of research results, or broadcasting realized or planned activities [40][41][42]. This constitutes the main reason to pay attention to an analysis of the communicated content.…”
Section: Value Of Social Media Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…They may be active on standard social networks such as Twitter and Instagram or on discussion forums [38], or they may insert their comments into articles in on-line news sites [39]. Such activities in social media take the form of expressing one's opinions, describing experiences, informing others of research results, or broadcasting realized or planned activities [40][41][42]. This constitutes the main reason to pay attention to an analysis of the communicated content.…”
Section: Value Of Social Media Analysismentioning
confidence: 99%
“…The aim of image analysis is primarily to provide further information on the context of the report, such as the location (for example a farmers' market or a railway station) or fashion trends [45]. The text analysis is then focused on identifying keywords, using social networking techniques based on frequency distributions [46], or eigenvector and betweenness centrality [41,42]. Another area of the text analysis is sentiment analysis, which focuses on identifying the users' feelings [47].…”
Section: Value Of Social Media Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to interact with farmers and vendors as well as the freshness of the products are the main factors, followed by quality, support of the local economy, and to a lesser extent the search for prepared food or arts, crafts, and prepared food. A more recent study based on consumer experience through self-expression on social networks found that consumers valued six major characteristics: #Organic, #Fresh, #Food, #Local, #Vegan, and #Healthy [73], indicating that some consumers had introduced new tendencies in their food choices according to a vegan and zero waste lifestyle.…”
Section: Consumersmentioning
confidence: 99%
“…For example, McGrath, Sherry Jr and Heisley [57] classify them by the time of day they arrive to the market and by their behavior-whether they shop right away or socialize first, and Hunt [56] divides them according to their motivations-lifestylers, seasonal shoppers, and utilitarians. Pilař et al [73] classify them according to their orientations. Therefore, there is not a single accepted typology of farmers' market consumer.…”
Section: Consumersmentioning
confidence: 99%